EFEKTIVITAS PENGGUNAAN SMARTPHONE DALAM MENDUKUNG PROSES BELAJAR DIKALANGAN PELAJAR SD NEGERI 01 MALANGJIWAN COLOMADU KARANGANYAR - Dian Esti Nurati, Lies Fajarwati Wijaya, Buddy Riyanto & (Transformasi, 2016)
This research is a descriptive-qualitative who try to describe the effectiveness of the use of thesmartphone in supporting the learning process among the students of elementary school 01Malangjiwan Colomadu Karanganyar. By using the interactive analysis models belonging to theMiles and Huberman, the results showed that the use of smartphones in the schools to improvestudents‟ communication activities with parents. The use of smartphones in the learningactivities in schools is hardly to be found, only for the purposes of learning, finding informationon the internet via smartphone done by the students while working on school assignments.Key words: smartphone, the use of smartphones, the effectiveness